THE USE OF LEARNING MEDIA THROUGH E-MODULES IN THE M. CARCASSI GUITAR COURSE AT THE MUSIC EDUCATION STUDY PROGRAM, STATE UNIVERSITY OF JAKARTA - Aristanisa, Vania (PT. Naureen Digital Education, 2024)
This study aims to develop and use the Learning Media E-Module of Matteo Carcassi Guitar Course at the Music Education Study Program, State University of Jakarta. This research is a type of Action Research research that is collaborated with development research. In the media development process, researchers use the ASSURE development model developed by Smaldino. The ASSURE development model consists of 6 stages, namely 1) Analyze characteristic learner, 2) State Objective, 3) Select Methode, Media and Materials, 4) Utilize Media and Materials, 5) Requires Learner Participation, 6) Evaluate and Revize. The data collection techniques used are interviews, observations, and questionnaires. Quantitative and qualitative data were analyzed using the Likert scale. Based on the conclusions of the research data, researchers obtained the following results: 1) The results of the analysis of student characteristics showed that 78.21% of the 21 students of the Music Education Study Program class of 2022, State University of Jakarta have an audio-visual learning style, so it is necessary to develop audiovisual-based media, namely E-Modules. 2) From the analysis of student needs, it shows that 90.5% of 21 students agree and are interested in developing E-Module-based learning media. 3) The e-module media that has been developed has passed validation by 2 experts including learning media experts and learning material experts. Based on validation that has been carried out by learning media experts, it resulted in a score of 98.4% so that it reached the